2013
DOI: 10.12932/ap0304.31.4.2013
|View full text |Cite
|
Sign up to set email alerts
|

A novel Bruton’s tyrosine kinase gene (BTK) invariant splice site mutation in a Malaysian family with X-linked agammaglobulinemia

Abstract: X-linked agammaglobulinemia (XLA) is a rare genetic disorder caused by mutations in the Bruton's tyrosine kinase (BTK) gene. These mutations cause defects in early B cell development. A patient with no circulating B cells and low serum immunoglobulin isotypes was studied as were his mother and sister. Monocyte BTK protein expression was evaluated by flow cytometry. The mutation was determined using PCR and followed by sequencing. Flow cytometry showed the patient lacked BTK protein expression in his monocytes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 12 publications
(18 reference statements)
1
6
0
Order By: Relevance
“…Similar to that observed in other studies, regardless of the histological classification, we disclosed a significant association between KIAA1549-BRAF gene fusion and its anatomical location to the cerebellum for LGG [21]. While we found the fusion in 61.3% of LGG, others detected it ranging from 59.1 to 89.7% of LGG [14,15,20,22].…”
Section: Discussionsupporting
confidence: 90%
“…Similar to that observed in other studies, regardless of the histological classification, we disclosed a significant association between KIAA1549-BRAF gene fusion and its anatomical location to the cerebellum for LGG [21]. While we found the fusion in 61.3% of LGG, others detected it ranging from 59.1 to 89.7% of LGG [14,15,20,22].…”
Section: Discussionsupporting
confidence: 90%
“…Patients with XLA are particularly susceptible to respiratory infections (12,13). In our patient, Lower respiratory tract secretion specimens were obtained on bronchoscopy at the time of endotracheal intubation for respiratory failure.…”
Section: Discussionmentioning
confidence: 99%
“…To date, 911 mutations in the BTK gene related to XLA have been deposited in the Human Gene Mutation Database (http:// The spectrum of these mutations includes missense mutations, nonsense mutations, splice site mutations, insertions, and deletions, with missense mutation being the most common. It has already been shown that these mutations can occur in the exons, introns, and promoters of the BTK gene [14,15]. In this study, six novel mutations were found (Table 2) The serious condition of these two patients was greatly alleviated once their diagnosis was established and IVIG treatment was initiated.…”
Section: Discussionmentioning
confidence: 60%